Your Story is Your Strength: Developing an Ethic of Care Through Transformative Learning - Gaffney, Jessica L. (School of Education, University of Wisconsin-Stevens Point, 2020)
The purpose of this study was to explore how transformative-learning theory supported the development of an ethics of care among seven students participating in a women’s leadership development program and how their learning can foster sustainability. Through a leadership program designed to infuse the development of an ethics of care into a general-education curriculum with transformative and feminist pedagogical techniques, participants were challenged to explore how their own experiences influence ways that they acquire knowledge and practiced care for others and the natural world. Data were collected through a process of narrative inquiry using a semi-structured interview format. Themes emerged through the use of storytelling that could help educators and administrators understand how to develop educational programs for women that support and value their unique experiences fostered by women’s ways of knowing.
Keywords: ethics of care; sustainability; leadership development program; feminine leadership; women's ways of knowing; education for sustainability